Chronic and acute modulator treatment restore wild-type-like activity and stability to the primary cystic fibrosis–causing CFTR variant - Mayuree Rodrat; James N. Charlick; David N. Sheppard (Proceedings of the National Academy of Sciences, 2026)
Elexacaftor-tezacaftor-ivacaftor has transformed the treatment of people with cystic fibrosis (CF) and the predominant cystic fibrosis transmembrane conductance regulator ( CFTR ) variant F508del by delivering the faulty channel to the plasma membrane and potentiating its activity. However, the action of elexacaftor-tezacaftor-ivacaftor on the molecular behavior of F508del-CFTR is unknown. Here, we investigated the impact of elexacaftor-tezacaftor-ivacaftor on individual human F508del-CFTR Cl − channels using the patch-clamp technique and cells heterologously expressing F508del-CFTR. Chronic treatment of F508del-CFTR-expressing cells with elexacaftor-tezacaftor-ivacaftor, but not pairs of CFTR modulators, stabilized F508del-CFTR, preventing channel deactivation in cell-free membrane patches and conferring upon it the current amplitude of wild-type CFTR with channel activity sustained at a level one-third that of wild-type CFTR. By incubating cells with different drug concentrations, we demonstrated that elexacaftor stabilizes the open-channel conformation of elexacaftor-tezacaftor-ivacaftor-rescued F508del-CFTR, while acute treatment of wild-type CFTR with elexacaftor increased current flow through the channel and potentiated channel gating. Of note, acute treatment of elexacaftor-tezacaftor-ivacaftor-rescued F508del-CFTR Cl − channels with elexacaftor and ivacaftor restored wild-type levels of channel activity to the CFTR variant, albeit its gating pattern was distinct from that of wild-type CFTR and characterized by infrequent prolonged bursts of channel openings. In conclusion, chronic treatment with elexacaftor-tezacaftor-ivacaftor plus acute treatment with elexacaftor and ivacaftor robustly corrects the processing, stability, and gating defects of F508del-CFTR. Our results reveal that elexacaftor is a triple-acting CFTR modulator with corrector, potentiator, and conduction activities, making it a valuable therapeutic to rescue CFTR variants with distinct molecular mechanisms of CFTR dysfunction.